Contribution to the knowledge of the Mallophaga (Phthiraptera, Amblycera, Ischnocera) of the Peruvian birds. Part 1 - Gomez-Puerta, Luis A. (2015)
Nine species of Mallophaga from Peruvian birds are reported in this work. Two Mallophaga Amblycera: Heteromenopon laticapitis y Menacanthus pici, as well as seven Mallophaga Ischnocera: Alcedoffula theresae, Brueelia brunneinucha, Chelopistes meleagridis, Columbicola columbae, Paragoniocotes aratingae, Penenirmus jungens y Saemundssonia (Saemundssonia) lari, were identified morphologically. A brief description of each chewing lice and discussion about their hosts and distribution is done.